1. The problem statement, all variables and given/known data dy/dx(x+dx) - dy/dx(x-dx) => d^2y/dx^2 when dx->0 can someone explain this step to me please? 2. Relevant equations The dx in the brackets should be sigma x 3. The attempt at a solution I know that dx -> means it tends to zero i think i might have missed something out that might make a difference to this step; it may be necessary to divide through the first line by dx (sigma x) to complete the step? Im stumped, i dont see how this works at all.